(untitled) (International Research Journal of Management and Social Sciences, 2024)
Ribā, commonly understood as usury or interest, has been a subject of significant debate and scrutiny within Islamic finance and broader societal contexts. This paper delves into the adverse impact of Ribā on society from multiple perspectives, encompassing economic, social, and ethical dimensions. Economically, Ribā fosters inequality by concentrating wealth in the hands of the lenders while burdening borrowers with perpetual debt. The interest-based financial system incentivizes profit over productivity, leading to speculative bubbles, financial crises, and widening wealth gaps. Moreover, Ribā discourages entrepreneurship and innovation, as individuals may opt for interest-based financing rather than seeking Sharia-compliant alternatives. Socially, Ribā exacerbates poverty and marginalization, particularly among vulnerable populations. High interest rates on loans and credit exacerbate the cycle of poverty, trapping individuals and communities in perpetual debt. This phenomenon disproportionately affects low-income households, perpetuating socio-economic disparities and hindering social mobility. Furthermore, the commodification of money through interest-based transactions undermines the values of solidarity and cooperation, eroding social cohesion and trust within communities. Ethically, Ribā contradicts the principles of fairness, justice, and compassion inherent in Islamic teachings. It exploits the financial vulnerability of individuals for personal gain, violating the principle of mutual benefit and harming the common good. The pursuit of excessive profits through interest contradicts the ethical imperative of responsible stewardship and sustainable development. The adverse impact of Ribā on society is multifaceted, encompassing economic inequality, social injustice, and ethical degradation. Addressing these challenges requires a holistic approach that promotes financial inclusion, equitable wealth distribution, and ethical finance practices. By adhering to the principles of justice, compassion, and mutual cooperation, societies can mitigate the adverse effects of Ribā and foster inclusive prosperity for all members.